What is the best imaging test for the diagnosis of acute appendicitis in children?. Issue 5 (May 2016) - Cobb, Hana; Henderson‐Drager, William; Braun, Michael M.
Abstract : Evidence‐Based Answer : A staged approach using ultrasound (US) followed by CT scan (if the US is equivocal) is effective in diagnosing acute appendicitis (sensitivity 99% and specificity 91%) (SOR: A, systematic review of diagnostic cohort studies and consistent cohort study). Triaging cases with a pediatric appendicitis score (PAS) prior to US and follow‐up with CT if the US is equivocal lowers sensitivity to 92% and increases specificity to 95% (SOR: B, prospective cohort trial). Follow‐up MRI after an equivocal US has a sensitivity of 100% and a specificity of 96% (SOR: B, retrospective cohort trial).